TRANSLATION SKILLS OF SHOISLOM SHOMUKHAMEDOV - Xulkar Murotova (International Journal of Literature and Language Studies, 2026)
This article explores the translation skills of renowned orientalist and translator Professor Shoislom Shomukhamedov in translating classical Persian-Tajik poetry into Uzbek. It analyzes in detail the scholar's unique style and mastery of preserving the aruz metric system, rhyme structure, and philosophical and Sufi content when translating the rubaiyat of Omar Khayyam, the ghazals of Hafiz Shirazi, and the epic poems of Ferdowsi.